2017
DOI: 10.1002/ajpa.23307
|View full text |Cite
|
Sign up to set email alerts
|

Transition to agriculture in South‐Eastern Arabia: Insights from oral conditions

Abstract: Oral conditions from the Neolithic coastal populations denote a diet mainly composed of unprocessed and abrasive food, with high protein and low carbohydrate intakes, and frequent stress episodes. Although Hafit populations display some changes in oral pathologies, which indicate modifications in their lifestyle and a diversification of the diet, no markers of high carbohydrate intakes were observed in our samples. The impact of agriculture on oral health appears clearly only from the Umm an-Nar period, and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 35 publications
0
20
0
5
Order By: Relevance
“…This intensified use of coastal areas perhaps reflects their greater ecological diversity and water availability (40,41). Omani coastal populations relied heavily on marine resources, as demonstrated at Ras al-Hamra (42,43) where bioarchaeological investigations revealed that the population was in poor overall health (44). On the island of Akab in the UAE, dugong bone mound (5.5 to 5.2 ka) excavations revealed that faunal remains were specially arranged, suggesting a monumental space (45), and perhaps the consequence of ritualized acts of consumption at a time of increased subsistence stress (21).…”
Section: Significancementioning
confidence: 99%
“…This intensified use of coastal areas perhaps reflects their greater ecological diversity and water availability (40,41). Omani coastal populations relied heavily on marine resources, as demonstrated at Ras al-Hamra (42,43) where bioarchaeological investigations revealed that the population was in poor overall health (44). On the island of Akab in the UAE, dugong bone mound (5.5 to 5.2 ka) excavations revealed that faunal remains were specially arranged, suggesting a monumental space (45), and perhaps the consequence of ritualized acts of consumption at a time of increased subsistence stress (21).…”
Section: Significancementioning
confidence: 99%
“…Many of the Neolithic sites lie at the mouth of wadi deltas or estuaries that supplied fresh water, and were therefore subject to rapid coastal sedimentation (Berger et al, ; Biagi & Nisbet, ; Woodroffe, ). As a consequence, their subsistence economy was often based, almost exclusively, on the exploitation of marine and mangrove swamp resources (Biagi & Nisbet, ; Munoz, ; Zazzo, Munoz, & Saliège, ; Zazzo et al, ). The Arabian Sea mangroves can be considered to have been highly productive on many levels for the prehistoric subsistence economies (Berger et al, ; Biagi & Nisbet, ; Tengberg, ).…”
Section: Neolithic Arabian Coastal Archaeology Context and State Of Tmentioning
confidence: 99%
“…By the early Bronze Age (Hafit period; c .3100–2600 BC), zooarchaeological studies indicate that domesticated animals were a major part of subsistence strategies alongside the plant products of oasis agriculture, forming an integrated agro‐pastoral system in south‐eastern Arabia (al‐Jahwari, ; Munoz, ; Tengberg, ; Uerpmann M. & Uerpmann, ). The increasing prevalence of domestic animals is demonstrated by their dominance in the majority of assemblages dating to this period.…”
Section: Humans and Animals In Late Prehistoric South‐eastern Arabiamentioning
confidence: 99%